Cable-Suspended Haptic Interface - Williams II, Robert L. (International Journal of Virtual Reality, 1998)
A cable-suspended haptic interface (CSHI) concept is presented. The goal is to create an input/output device to provide six-degree-of-freedom (dof) wrench (force and moment) feedback to a human operator in virtual reality or remote applications. Compared to commercially-available haptic interfaces for virtual reality applications, the present concept is driving for lighter, safer, crisper, more dexterous, and more economical operation. The CSHI concept is presented, along with the required mathematical transformations for use of the device.